TREATMENT OF OPEN TIBIA FRACTURE WITH FLEXIBLE MEDULLARY NAILING - M Rouhi, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Tibia fracture is one of the most common long bone fractures in body and primary treatment of open fracture always worries surgeons. The aim of this study was to evaluate the treatment of open tibia fractures by flexible medullary nailing.METHODS: This descriptive-analytical study was performed on 44 patients suffering from open tibial fractures treated with flexible medullary nails in Shahid Beheshti and Yahyanejad hospitals from 1998-2001. In this study with limited incision, fixation of open fractures (gustilo type I to type IIIA) was done by 2-3 nails (3mm or 3.5mm). Demographic information associated with variables such as infection, for 1.5 years followed up in patients and data was analyzed by ANOVA test. FINDINGS: Mean age of patients was 29.8 years and 37(84.1%) patients were male. The average time of :::union::: was 6.1 months. There were 2(4.5%) patients with deep infection and 7(15.9%) with superfacial infection. Delayed :::union::: was seen in 4(9.1%) patients and mal:::union::: was seen in 1(2.3%) patient and there was not non-:::union:::. CONCLUSION: Results of this study showed that flexible medullary nailing is a reliable method for treatment of open tibia fractures.